Assessment of early response biomarkers in relation to long‐term survival in patients with HER2‐negative breast cancer receiving neoadjuvant chemotherapy plus bevacizumab: Results from the Phase II PROMIX trial. Issue 3 (13th October 2017) - Kimbung, Siker; Markholm, Ida; Bjöhle, Judith; Lekberg, Tobias; von Wachenfeldt, Anna; Azavedo, Edward; Saracco, Ariel; Hellström, Mats; Veerla, Srinivas; Paquet, Eric; Bendahl, Pär‐Ola; Fernö, Mårten; et al.
Abstract : Pathologic complete response (pCR) is a predictor for favorable outcome after neoadjuvant treatment in early breast cancer. Modulation of gene expression may also provide early readouts of biological activity and prognosis, offering the possibility for timely response‐guided treatment adjustment. The role of early transcriptional changes in predicting response to neoadjuvant chemotherapy plus bevacizumab was investigated. One‐hundred‐and‐fifty patients with large, operable and locally advanced HER2‐negative breast cancer received epirubicin and docetaxel, with the addition of bevacizumab. Patients underwent tumor biopsies at baseline, after Cycle 2 and at the time of surgery. The primary end point, pCR, and its relation with the secondary endpoints event‐free survival (EFS), overall survival (OS) and gene expression profiles, are reported. The pCR rate was 13% (95% CI 8.6–20.2), with significantly more pCRs among triple‐negative [28% (95% CI 14.8–45.4)] than among hormone receptor positive (HR+) tumors [9% (95% CI 4.6–16.3); (OR = 3.9 [CI = 1.5–10.3])]. pCR rates were not associated with EFS or OS. PAM50 subtypes significantly changed after Cycle 2 ( p = 0.03) and an index of absolute changes in PAM50 correlations between these time‐points was associated with EFS [HR = 0.62 (CI = 0.3–1.1)]. In univariable analyses, signatures for angiogenesis, proliferation, estrogen receptor signaling, invasion and metastasis, and immune response, measured after Cycle 2, were associated with pCR in HR+ tumors. Evaluation of changes in molecular subtypes and other signatures early in the course of neoadjuvant treatment may be predictive of pCR and EFS. These factors may help guide further treatment and should be considered when designing neoadjuvant trials. Abstract : What's new? It's a good sign for a patient's prognosis if, after pre‐operative chemotherapy, no breast cancer cells survive. But this metric isn't perfect, and varies depending on the tumor's molecular subtype. Here, the authors analyzed changes in gene expression brought on by chemotherapy. They analyzed molecular markers in biopsies from 150 breast cancer patients at three time points: baseline, after 2 cycles of neoadjuvant therapy, and right before surgery. Neoadjuvant chemotherapy significantly changed the tumor's gene expression profile, they found, and these changes could have predictive value: a bigger change between baseline and Cycle 2 correlated with longer event‐free survival.